IMPROVING STUDENTS’ PRONUNCIATION MASTERY THROUGH LEARNING BY USING MEDIAS - Humiras Betty Sihombing (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2018)
This study deals with the fourth semester students of English Department of Letter Faculty in Darma Agung University. The objective of this study is to investigate how well using related media such as English songs and English movies improves students’ pronunciation. It uses Classroom Action Research in which the subject the subject of this study is the fourth semester students of English Department of Letter Faculty in Darma Agung University. It is showed the improvement of students’ score based on the range of the pre-test (55.3) to the posttest in Cycle II (85.4). Thus, the use of relate media such as English Songs and English Movies improves students’ pronunciation well